Late Sac Rupture due to a Type IV Endoleak after Previous Endovascular Aortic Aneurysm Repair: A Case Report - Filis, Konstantinos; Zarmakoupis, Constantinos; Karantzikos, Georgios; Sigala, Frangiska; Bazigos, Gerasimos; Galyfos, George (Frontiers in Surgery, 2017)
Type IV endoleaks have been identified as endoleaks of low flow, and rupture risk has been estimated to be minimal in literature. Therefore, conservative treatment has been recommended in most cases. We are presenting a rare case of late rupture due to type IV endoleak that was treated with open repair applying a novel surgical technique.